2015
DOI: 10.1186/s12913-015-1230-4
|View full text |Cite
|
Sign up to set email alerts
|

Using meta-regression analyses in addition to conventional systematic review methods to examine the variation in cost-effectiveness results – a case study

Abstract: BackgroundSystematic reviews of cost-effectiveness analyses summarize results and describe study characteristics. Variability in the study results is often explained qualitatively or based on sensitivity analyses of individual studies. However, variability due to input parameters and study characteristics (e.g., funding or study quality) is often not statistically explained. As a case study, a systematic review on the cost-effectiveness of drug-eluting stents (DES) versus bare-metal stents (BMS) using meta-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Only in the case where the SR-CCEO's objective is very narrowly focused is it feasible to explore associations between modeling methods and costs or cost-effectiveness outcomes using meta-regression analysis. 60 If methodologic factors that can potentially explain differences between the studies' outcomes are identified, they should be reported.…”
Section: Exploring Heterogeneity In Datamentioning
confidence: 99%
“…Only in the case where the SR-CCEO's objective is very narrowly focused is it feasible to explore associations between modeling methods and costs or cost-effectiveness outcomes using meta-regression analysis. 60 If methodologic factors that can potentially explain differences between the studies' outcomes are identified, they should be reported.…”
Section: Exploring Heterogeneity In Datamentioning
confidence: 99%